10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
PurposeTo examine multiple implementations of the Change Club (CC) curriculum.ApproachCompiled information about studies that used the CC curriculum.SettingTen research studies using the CC curriculum.InterventionCivic engagement policy, systems, and environmental change (PSE) curriculum, in which small groups follow a stepwise process to change physical activity- and/or food-related aspects of their community.MethodReviewed study records to describe multiple implementations of the CC curriculum.ResultsThe studies varied in terms of U.S. region, inclusion criteria, number of CC members, duration, and outcomes measured. Curriculum implementation varied, with session lengths varying from 30 minutes to multiple hours. Some studies included other interventions such as walking clubs. Across the 10 studies, there were 62 CCs, with seed monies ranging from $600 to $5000. The majority of CCs were facilitated by a USDA Cooperative Extension agent; 95% of CCs successfully completed a PSE project. Sixty-one percent of projects included physical activity elements only.ConclusionKey recommendations include the importance of involving stakeholders, encouraging positive CC group dynamics, ensuring CC members understand the time and effort of PSE projects, identifying and cultivating facilitators that have capacity and can transition the project to group members, completing CC modules in a short period of time to retain members, and including group members who have existing community connections.Clinical Trial #sNCT05002660, NCT05677906, NCT05867433.